Wear-resistant flame-retardant vehicle paint and spraying process thereof

By using water-based polyurethane and aqueous acrylic resin in automotive paint, and by specific treatment of tungsten carbide and quartz sand, the problem of insufficient wear resistance and flame retardancy of automotive paint is solved, achieving high-performance and safe paint.

CN119307141AInactive Publication Date: 2025-01-14SHANGHAI REAL INDAL
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411847750.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing automotive paints have poor wear resistance and poor flame retardant effects, which cannot meet high performance and safety requirements, especially in high temperature and fire scenarios.

Method used

Using water-based polyurethane and aqueous acrylic resin as the base paint, quartz sand is treated with chitosan treatment of tungsten carbide and silane coupling agent to form a topcoat with high hardness and flame retardancy, combined with polyamide wax and modified quartz sand , enhance the wear resistance and flame retardant properties of paint.

Benefits of technology

Excellent wear resistance and flame retardancy of paint are achieved, ensuring good performance in high temperature and fire scenarios, extending service life and preventing flame spread.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to wear-resistant flame-retardant automotive paint and a spraying process thereof, and belongs to the technical field of paint. The vehicle paint comprises a primer, a colored paint and a finishing paint, the finishing paint takes waterborne polyurethane and waterborne acrylic resin as base materials, the wear resistance of the paint is improved by adding a wear-resistant filler, the flame retardance of the paint is improved by adding a flame retardant, and excellent performance is kept under the action of other auxiliaries. And through two-time primer spraying, one-time colored paint spraying and one-time finish paint spraying, the paint forms a uniform paint layer on the surface of the vehicle body, so that excellent adhesive force, wear resistance and flame retardance are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of paints and relates to a wear-resistant and flame-retardant automotive paint and a spraying process thereof. Background Art

[0002] Paint is a chemical mixture coating that can firmly cover the surface of an object for protection, decoration, marking and other special purposes.

[0003] Car paint is different from other paints. Because cars are expensive and they experience the weather all year round, the performance requirements for car paint are extremely high. Car paint should not only have good mechanical properties, good fullness, and high gloss, but also have good adhesion, high hardness, and strong scratch resistance. At the same time, it should have excellent weather resistance, scratch resistance, wear resistance, gloss continuity, and excellent resistance to gasoline, alcohol, acid, alkali, and salt spray. However, existing car paints have poor wear resistance and do not have anti-mark function. Paints are often used on the surface of objects to protect them, and flame-retardant paints used for flame-retardant, fire-resistant, and highly corrosion-resistant color-coated plates need to have flame-retardant, high-temperature resistant, and fire-resistant properties to delay the spread of fire and provide sufficient time for the arrival of the fire brigade; however, the flame-retardant effect of the currently commonly used flame-retardant paints is poor, so it is necessary to develop a wear-resistant and flame-retardant car paint. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant and flame-retardant automotive paint and a spraying process thereof. The paint prepared by the present invention has excellent wear resistance and flame retardancy.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A wear-resistant flame-retardant automotive paint, comprising a primer, a color paint and a topcoat, wherein the topcoat comprises the following raw materials in parts by weight: 35~40 parts of waterborne polyurethane, 50~70 parts of waterborne acrylic resin emulsion, 0.5~1 parts of defoaming agent, 5~8 parts of film-forming aid, 0.5~1 parts of wetting agent, 3~6 parts of wear-resistant filler, 3~7 parts of flame retardant, 0.3 parts of triethanolamine, 0.3~0.6 parts of leveling agent, 5~10 parts of deionized water; The preparation process of the wear-resistant filler is as follows: Chitosan was dissolved in an acetic acid aqueous solution with a mass fraction of 5% to obtain a chitosan solution, wherein the mass fraction of the chitosan solution was 13-17%, the temperature was maintained at 65°C and the speed was 300r / min for 45min, tungsten carbide was continuously added, the speed was maintained for 2-5h, and the mixture was dried at 95-105°C for 8-12h to obtain pretreated tungsten carbide; 30-40 parts of pretreated tungsten carbide and 80-100 parts of toluene are uniformly mixed, and then 10-15 parts of polyamide wax are added, and stirred at a speed of 100-150 r / min for 40-60 min at room temperature, and the speed is increased to 300-500 r / min and stirred for 2-3 h, and then freeze-dried at -60°C for 6 h, and then ball-milled at a speed of 300 r / min for 3 h in a ball mill, and then passed through a 200-mesh sieve to obtain the wear-resistant filler; The preparation process of the flame retardant is as follows: Silane coupling agent KH550 was mixed with deionized water and ethanol in a volume ratio of 1:10 to prepare a KH550 solution with a mass fraction of 5-10%. Quartz sand was immersed in the KH550 solution, and then ultrasonically dispersed for 30 minutes, heated to 100 °C in a water bath and stirred for 1.5 hours. The dried solid was dried in a 95 °C constant temperature forced air drying oven for 10 hours to obtain a dry solid. The dried solid and polysilsesquioxane in a mass ratio of 20:(4-7) were then ground in a ball mill at a speed of 400 r / min for 4 hours to obtain modified quartz sand. Modified quartz sand, ammonium polyphosphate and zirconium phosphate in a mass ratio of (5-8):10:10 are ground by a ball mill at a speed of 300 r / min for 2 h to uniformly disperse them to obtain the flame retardant.

[0006] As a preferred technical solution of the present invention, the film-forming aid is dipropylene glycol methyl ether.

[0007] As a preferred technical solution of the present invention, the defoaming agent is one of BYK011, BYK022 and BYK024.

[0008] As a preferred technical solution of the present invention, the wetting agent is one of BYK349 ​​and BYK348.

[0009] As a preferred technical solution of the present invention, the leveling agent is polyether-modified polydimethylsiloxane.

[0010] A spraying process for wear-resistant flame-retardant automotive paint comprises the following steps: S1. Pretreatment: Degreasing, decontamination and electrostatic dust removal are performed on the surface of the car, wherein the surface static voltage is less than 600 volts; S2, spraying primer: spray primer on the surface of the car after electrostatic dust removal, dry it at room temperature for 35-45 minutes, spray primer for the second time, continue drying and curing for 40-50 minutes to obtain a primer layer, wherein the parameters during spraying are: spraying pressure of 0.45-0.55MPa, spraying distance of 15-20cm; S3, spray paint: spray paint on the surface of the primer layer, dry it at room temperature for 40-50 minutes to form a paint layer, wherein the spraying pressure is 0.65-0.75MPa, and the spraying distance is 20-30cm; S4, spray paint: According to the weight proportions, waterborne polyurethane, triethanolamine and waterborne acrylic resin emulsion were stirred at a speed of 250 r / min for 30-40 min, and then wear-resistant filler and wetting agent were added and stirred for 35 min, and then flame retardant, defoaming agent and leveling agent were added and stirred at a speed of 350 r / min for 25-35 min, and finally film-forming aid and deionized water were added and stirred for 45 min to obtain topcoat; Spray the topcoat on the surface of the color paint layer and dry it at room temperature for 1-2 hours to form a topcoat layer. Control the spraying pressure to 0.9-1.1 MPa and the spraying distance to 30-45 cm. S5, drying: drying at 140-150° C. for 15-25 min to complete the spraying of the wear-resistant flame-retardant automotive paint.

[0011] As a preferred technical solution of the present invention, the thickness of the primer layer is 15-20 μm.

[0012] As a preferred technical solution of the present invention, the thickness of the color paint layer is 20-30 μm.

[0013] As a preferred technical solution of the present invention, the thickness of the topcoat layer is 30-45 μm.

[0014] The vehicle paint prepared by the present invention includes a primer, a color paint and a topcoat, wherein tungsten carbide is used as a wear-resistant filler in the topcoat. Tungsten carbide has high hardness and wear resistance, and has a high melting point and thermal stability, and can maintain good performance in a high temperature environment.

[0015] In the present invention, tungsten carbide is first treated with chitosan solution to enhance the activity of the tungsten carbide surface. There are a large number of functional groups such as hydroxyl and amino groups in chitosan molecules, which can enhance the activity of the tungsten carbide surface. The enhancement of this activity helps the subsequent polyamide wax to better adhere to the tungsten carbide surface and improve the binding force between the two. In addition, chitosan has good film-forming properties and wettability, and can form a uniform film on the tungsten carbide surface. This film can improve the wettability of the tungsten carbide surface, making it easier for the polyamide wax to spread during the coating process to form a uniform coating.

[0016] Chitosan, as an intermediate layer, can fill the tiny defects and pores on the surface of tungsten carbide to form a dense film. This film can serve as a transition layer between polyamide wax and tungsten carbide to enhance the bonding force between the two, and can also further improve the compatibility of polyamide wax and tungsten carbide.

[0017] Polyamide wax has excellent thixotropic properties and can form a strong network structure in the paint, thereby providing excellent anti-sagging and anti-settling capabilities. Polyamide wax has good chemical stability and can remain stable in a variety of chemical environments, and is not prone to decomposition or deterioration. In addition, polyamide wax itself has a certain wear resistance, which can reduce friction and wear and extend service life. Therefore, tungsten carbide modified with chitosan and polyamide wax has better performance.

[0018] The melting point of quartz sand is very high, usually above 1300°C. When a material containing quartz sand encounters a fire source, the quartz sand can form a heat-insulating layer on the surface of the material, which can prevent heat from being transferred into the material, thereby slowing down the burning speed of the material. In the present invention, the quartz sand is first treated with a silane coupling agent KH550, which can react with the hydroxyl groups on the surface of the quartz sand to generate silicon-oxygen-silicon bonds (Si-O-Si) and form a chemical bonding reaction. This chemical bonding can enhance the polarity of the surface of the quartz sand. The silane coupling agent helps the quartz sand and polysilsesquioxane to mix through a bridge effect, thereby improving the compatibility between the two.

[0019] During the combustion process, polysilsesquioxane can quickly form a dense silicon-oxygen-carbon layer on the surface of the material. This carbon layer has excellent heat insulation and oxygen isolation properties, which can effectively prevent the transfer of heat and oxygen, thereby slowing down or stopping the combustion process. The silicon and oxygen elements in silicon-based polysilsesquioxane can participate in free radical reactions during the combustion process, interrupting the transfer of the combustion chain, thereby slowing down or terminating the combustion process. Polysilsesquioxane has excellent heat resistance and flame retardancy. After combining it with quartz sand, the modified quartz sand can significantly improve the flame retardancy level of the paint. When a fire occurs, the modified quartz sand can form a dense protective layer on the surface of the paint to prevent the spread of flames and the transfer of heat, thereby delaying the expansion of the fire. At the same time, due to the treatment with polysilsesquioxane, the modified quartz sand can be more compatible with the base material in the paint, so the adhesion and durability of the paint can be improved. In addition, the dispersibility and stability of the modified quartz sand in the paint are improved, which helps to reduce the agglomeration and precipitation phenomena in the paint and improve the uniformity and stability of the paint. This helps ensure that the paint maintains consistent performance and quality during the application and curing process.

[0020] The flame retardant is prepared by mixing modified quartz sand with ammonium polyphosphate and zirconium phosphate. Ammonium polyphosphate will decompose when heated to produce strong dehydrating agents such as poly / polyphosphoric acid. These substances will promote the dehydration and carbonization of the surface of organic matter to form a heat-insulating layer. At the same time, non-volatile phosphorus oxides and polyphosphoric acid will cover the surface of the substrate and isolate the air, thereby achieving the purpose of flame retardancy. Because it contains nitrogen, ammonium polyphosphate decomposes when heated to release gases such as nitrogen and ammonia. These gases are not easy to burn and play a role in diluting the oxygen in the air, thereby blocking the supply of oxygen and further enhancing the flame retardant effect.

[0021] When the composite material burns, zirconium phosphate will release crystal water, which can take away some heat, reduce the concentration of combustibles in the gas phase combustion zone, and delay the thermal decomposition of the polymer matrix, thereby reducing the combustion rate. In addition, the decomposition products of zirconium phosphate can form a protective film covering the surface of the polymer. This protective film can not only block the mass transfer process of volatile products generated by polymer degradation to the gas phase, but also block the feedback of heat generated by gas phase combustion to the condensed phase. Through the combination of the three, different flame retardant mechanisms can achieve better flame retardant effects.

[0022] Beneficial effects of the present invention: The automotive paint of the present invention comprises primer, color paint and topcoat, wherein the topcoat is made of waterborne polyurethane and waterborne acrylic resin as base materials, and the waterborne polyurethane has excellent wear resistance and flexibility, and can ensure that the coating is not easy to wear and crack during long-term use. The waterborne acrylic resin has good hardness and adhesion, and can enhance the overall strength and stability of the coating. The wear resistance of the paint is improved by adding wear-resistant fillers, and the flame retardancy of the paint is improved by adding flame retardants, and excellent performance is maintained under the action of other additives. And by spraying primer twice, spraying color paint once and spraying topcoat once, the paint is formed into a uniform paint layer on the surface of the vehicle body, thereby maintaining excellent adhesion and wear resistance and flame retardancy. DETAILED DESCRIPTION

[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0024] In the following examples and comparative examples: The primer and color paint used in the present invention are both commercially available conventional products; Waterborne polyurethane: purchased from Changzhou Baichang Coating Technology Co., Ltd., product number: BZ-7; Water-based acrylic resin emulsion: purchased from Wuhan Penglei Biotechnology Co., Ltd.; Polyether-modified polydimethylsiloxane: purchased from Shanghai Kelaman Reagent Co., Ltd. Dipropylene glycol methyl ether: purchased from Shanghai Jiader Chemical Technology Co., Ltd. BYK024: purchased from Shanghai Ruwei Chemical Co., Ltd.; BYK349: purchased from Dongguan Hongrui Chemical Co., Ltd.; Triethanolamine: purchased from Shanghai Fangye Chemical Co., Ltd. Chitosan: purchased from Shandong Haiyihua Biotechnology Co., Ltd.; Tungsten carbide: purchased from Yumu (Ningbo) New Materials Co., Ltd., product number: DSADD; KH550: purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Quartz sand: purchased from Shanghai Kanglang Biotechnology Co., Ltd., product number: KL817378; Ammonium polyphosphate: purchased from Shanghai Juqian New Materials Development Co., Ltd. Zirconium phosphate: purchased from Shandong Yonglida New Materials Technology Co., Ltd., product number: JZYL-D; Polysilsesquioxane: purchased from Shanghai Myrel Biochemical Technology Co., Ltd.; Polyamide wax: purchased from Shanghai Kaiyin Chemical Co., Ltd., the brand is Lubrizol Lanco A1601.

[0025] Example 1 The topcoat comprises the following raw materials in parts by weight: 35 parts of waterborne polyurethane, 50 parts of waterborne acrylic resin emulsion, 0.5 parts of BYK024, 5 parts of dipropylene glycol methyl ether, 0.5 parts of BYK349, 3 parts of wear-resistant filler, 3 parts of flame retardant, 0.3 parts of triethanolamine, 0.3 parts of polyether modified polydimethylsiloxane, 5 parts of deionized water; The preparation process of the wear-resistant filler is as follows: Chitosan was dissolved in an acetic acid aqueous solution with a mass fraction of 5% to obtain a chitosan solution, wherein the mass fraction of the chitosan solution was 13%, the temperature was maintained at 65°C and the speed was 300r / min for 45min, tungsten carbide was continuously added, the speed was maintained for 2h, and the mixture was dried at 95°C for 8h to obtain pretreated tungsten carbide; 30 parts of pretreated tungsten carbide and 80 parts of toluene were evenly mixed, and then 10 parts of polyamide wax were added, stirred at a speed of 100 r / min for 40 minutes at room temperature, increased to 300 r / min and stirred for 2 hours, freeze-dried at -60°C for 6 hours, ball-milled in a ball mill at a speed of 300 r / min for 3 hours, and then passed through a 200-mesh sieve to obtain the wear-resistant filler.

[0026] The preparation process of flame retardant is as follows: Silane coupling agent KH550 was mixed with deionized water and ethanol in a volume ratio of 1:10 to prepare a KH550 solution with a mass fraction of 5%. Quartz sand was immersed in the KH550 solution, and then ultrasonically dispersed for 30 minutes, heated to 100 °C in a water bath and stirred for 1.5 hours. The dried solid was dried in a 95 °C constant temperature forced air drying oven for 10 hours to obtain a dry solid. The dried solid and polysilsesquioxane in a mass ratio of 20:4 were then ground in a ball mill at a speed of 400 r / min for 4 hours to obtain modified quartz sand. Modified quartz sand, ammonium polyphosphate and zirconium phosphate in a mass ratio of 5:10:10 were ground by a ball mill at a speed of 300 r / min for 2 h to uniformly disperse them to obtain the flame retardant.

[0027] S1. Pretreatment: Degreasing, decontamination and electrostatic dust removal are performed on the surface of the car, wherein the surface static voltage is less than 600 volts; S2, spraying primer: spraying primer on the surface of the car after electrostatic dust removal, drying at room temperature for 35 minutes, spraying primer for the second time, and continuing to dry and cure for 40 minutes to obtain a primer layer, wherein the parameters during spraying are: spraying pressure of 0.45MPa, spraying distance of 15cm; S3, spraying paint: spray paint on the surface of the primer layer, and dry it at room temperature for 40 minutes to form a paint layer, wherein the spraying pressure is 0.65MPa and the spraying distance is 20cm; S4, spray paint: According to the weight proportions, waterborne polyurethane, triethanolamine and waterborne acrylic resin emulsion were stirred at a speed of 250 r / min for 30 min, and then wear-resistant filler and BYK349 ​​were added and stirred for 35 min, and then flame retardant, BYK024 and polyether-modified polydimethylsiloxane leveling agent were added and stirred at a speed of 350 r / min for 25 min, and finally film-forming aid and deionized water were added and stirred for 45 min to obtain a topcoat; Spray the topcoat on the surface of the color paint layer and dry it at room temperature for 1 hour to form a topcoat layer. Control the spraying pressure to 0.9MPa and the spraying distance to 30cm. S5, drying: drying at 140° C. for 15 min to complete the spraying of the wear-resistant flame-retardant automotive paint.

[0028] The thickness of the primer layer is 15 μm, the thickness of the color paint layer is 20 μm, and the thickness of the topcoat layer is 30 μm.

[0029] Example 2 The topcoat comprises the following raw materials in parts by weight: 37 parts of waterborne polyurethane, 60 parts of waterborne acrylic resin emulsion, 0.7 parts of BYK024, 6 parts of dipropylene glycol methyl ether, 0.7 parts of BYK349, 5 parts of wear-resistant filler, 5 parts of flame retardant, 0.3 parts of triethanolamine, 0.5 parts of polyether modified polydimethylsiloxane, 8 parts of deionized water; The preparation process of the wear-resistant filler is as follows: Chitosan was dissolved in an acetic acid aqueous solution with a mass fraction of 5% to obtain a chitosan solution, wherein the mass fraction of the chitosan solution was 15%, the temperature was maintained at 65°C and the speed was 300r / min for 45min, tungsten carbide was continuously added, the speed was maintained for 3h, and the mixture was dried at 100°C for 10h to obtain pretreated tungsten carbide; 35 parts of pretreated tungsten carbide and 90 parts of toluene were evenly mixed, and then 13 parts of polyamide wax were added, stirred at a speed of 130 r / min at room temperature for 50 minutes, increased to a speed of 400 r / min and stirred for 2.5 hours, freeze-dried at -60°C for 6 hours, ball-milled in a ball mill at a speed of 300 r / min for 3 hours, and then passed through a 200-mesh sieve to obtain the wear-resistant filler.

[0030] The preparation process of flame retardant is as follows: The silane coupling agent KH550 was mixed with deionized water and ethanol in a volume ratio of 1:10 to prepare a KH550 solution with a mass fraction of 8%. Quartz sand was immersed in the KH550 solution, and then ultrasonically dispersed for 30 minutes, heated to 100 °C in a water bath and stirred for 1.5 hours. The dried solid was dried in a 95 °C constant temperature forced air drying oven for 10 hours to obtain a dry solid. The dried solid and polysilsesquioxane in a mass ratio of 20:6 were then ground in a ball mill at a speed of 400 r / min for 4 hours to obtain modified quartz sand. Modified quartz sand, ammonium polyphosphate and zirconium phosphate in a mass ratio of 6:10:10 were ground by a ball mill at a speed of 300 r / min for 2 h to uniformly disperse them to obtain the flame retardant.

[0031] S1. Pretreatment: Degreasing, decontamination and electrostatic dust removal are performed on the surface of the car, wherein the surface static voltage is less than 600 volts; S2, spraying primer: spraying primer on the surface of the car after electrostatic dust removal, drying at room temperature for 40 minutes, spraying primer for the second time, and continuing to dry and cure for 45 minutes to obtain a primer layer, wherein the parameters during spraying are: spraying pressure of 0.5MPa, spraying distance of 18cm; S3, spraying paint: spray paint on the surface of the primer layer, dry it at room temperature for 46 minutes to form a paint layer, wherein the spraying pressure is 0.7MPa and the spraying distance is 26cm; S4, spray paint: According to the weight proportions, waterborne polyurethane, triethanolamine and waterborne acrylic resin emulsion were stirred at a speed of 250 r / min for 34 min, and then wear-resistant filler and BYK349 ​​were added and stirred for 35 min, and then flame retardant, BYK024 and polyether-modified polydimethylsiloxane leveling agent were added and stirred at a speed of 350 r / min for 30 min, and finally film-forming aid and deionized water were added and stirred for 45 min to obtain a topcoat; Spray the topcoat on the surface of the color paint layer and dry it at room temperature for 1.5 hours to form a topcoat layer. Control the spraying pressure to 1MPa and the spraying distance to 38cm. S5, drying: drying at 145° C. for 20 minutes to complete the spraying of the wear-resistant flame-retardant automotive paint.

[0032] The thickness of the primer layer is 18 μm, the thickness of the color paint layer is 26 μm, and the thickness of the topcoat layer is 38 μm.

[0033] Example 3 The topcoat comprises the following raw materials in parts by weight: 40 parts of waterborne polyurethane, 70 parts of waterborne acrylic resin emulsion, 1 part of BYK024, 8 parts of dipropylene glycol methyl ether, 1 part of BYK349, 6 parts of wear-resistant filler, 7 parts of flame retardant, 0.3 parts of triethanolamine, 0.6 parts of polyether modified polydimethylsiloxane, 10 parts of deionized water; The preparation process of the wear-resistant filler is as follows: Chitosan was dissolved in an acetic acid aqueous solution with a mass fraction of 5% to obtain a chitosan solution, wherein the mass fraction of the chitosan solution was 17%, the temperature was maintained at 65°C and the speed was 300r / min for 45min, tungsten carbide was continuously added, the speed was maintained for 5h, and the mixture was dried at 105°C for 12h to obtain pretreated tungsten carbide; 40 parts of pretreated tungsten carbide and 100 parts of toluene were evenly mixed, and then 15 parts of polyamide wax were added, and stirred at a speed of 150 r / min for 60 minutes at room temperature, and the speed was increased to 500 r / min and stirred for 3 hours. After freeze-drying at -60°C for 6 hours, the mixture was ball-milled in a ball mill at a speed of 300 r / min for 3 hours, and then passed through a 200-mesh sieve to obtain the wear-resistant filler.

[0034] The preparation process of flame retardant is as follows: Silane coupling agent KH550 was mixed with deionized water and ethanol in a volume ratio of 1:10 to prepare a KH550 solution with a mass fraction of 10%. Quartz sand was immersed in the KH550 solution, and then ultrasonically dispersed for 30 minutes, heated to 100 °C in a water bath, stirred for 1.5 hours, and dried in a 95 °C constant temperature forced air drying oven for 10 hours to obtain a dry solid. The dry solid and polysilsesquioxane in a mass ratio of 20:7 were then ground in a ball mill at a speed of 400 r / min for 4 hours to obtain modified quartz sand. Modified quartz sand, ammonium polyphosphate and zirconium phosphate in a mass ratio of 8:10:10 were ground by a ball mill at a speed of 300 r / min for 2 h to uniformly disperse them to obtain the flame retardant.

[0035] S1. Pretreatment: Degreasing, decontamination and electrostatic dust removal are performed on the surface of the car, wherein the surface static voltage is less than 600 volts; S2, spraying primer: spraying primer on the surface of the car after electrostatic dust removal, drying at room temperature for 45 minutes, spraying primer for the second time, and continuing to dry and cure for 50 minutes to obtain a primer layer, wherein the parameters during spraying are: spraying pressure of 0.55MPa, spraying distance of 20cm; S3, spraying paint: spray paint on the surface of the primer layer, and dry it at room temperature for 50 minutes to form a paint layer, wherein the spraying pressure is 0.75MPa and the spraying distance is 30cm; S4, spray paint: According to the weight proportions, waterborne polyurethane, triethanolamine and waterborne acrylic resin emulsion were stirred at a speed of 250 r / min for 40 min, and then wear-resistant filler and BYK349 ​​were added and stirred for 35 min, and then flame retardant, BYK024 and polyether-modified polydimethylsiloxane leveling agent were added and stirred at a speed of 350 r / min for 35 min, and finally film-forming aid and deionized water were added and stirred for 45 min to obtain a topcoat; Spray the topcoat on the surface of the color paint layer and dry it at room temperature for 2 hours to form a topcoat layer. Control the spraying pressure to 1.1MPa and the spraying distance to 45cm. S5, drying: drying at 150° C. for 25 min to complete the spraying of the wear-resistant flame-retardant automotive paint.

[0036] The thickness of the primer layer is 20 μm, the thickness of the color paint layer is 30 μm, and the thickness of the topcoat layer is 45 μm.

[0037] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the tungsten carbide in Comparative Example 1 is not pretreated, and the other operations are the same.

[0038] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the wear-resistant filler in Comparative Example 2 is tungsten carbide without any modification treatment, and the other operations are the same.

[0039] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the quartz sand in Comparative Example 3 is not modified, and the other operations are the same.

[0040] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the preparation process of the flame retardant in Comparative Example 4 is as follows: ammonium polyphosphate and zirconium phosphate in a mass ratio of 1:1 are ground by a ball mill at a speed of 300 r / min for 2 h to make them evenly dispersed to obtain a flame retardant, and the other operations are the same.

[0041] Performance Test: The topcoats prepared in Examples 1-3 and Comparative Examples 1-4 were respectively applied on the surface of the steel plate, and the amount of paint was controlled to be 40 g / m 2 , perform the following tests: 1. Wear resistance: The wear resistance of the present invention was measured by using a JM IV abrasion tester and a rotating friction rubber wheel method, and the average value of the weight loss rate after 100 grinding revolutions was tested. The load was 10 N, the rotation speed was 80 r / min, the test temperature was 25° C., and the relative humidity was 50%. The results are shown in Table 1: Table 1

[0042] 2. Use an oxygen index meter to test the limiting oxygen index of the material, and use a horizontal and vertical combustion instrument to test the combustion grade of the material. The sample length is 100mm, the width is 10±0.5mm, and the thickness is 10±0.5mm. The higher the limiting oxygen index, the better the flame retardancy. The test results are shown in Table 2: Table 2

[0043] According to the above data, it can be seen that the paint prepared by the present invention has good flame retardancy and wear resistance.

[0044] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A wear-resistant flame-retardant automotive paint, characterized in that: The wear-resistant flame-retardant automotive paint comprises a primer, a color paint and a topcoat, wherein the topcoat comprises the following raw materials in parts by weight: 35~40 parts of waterborne polyurethane, 50~70 parts of waterborne acrylic resin emulsion, 0.5~1 parts of defoaming agent, 5~8 parts of film-forming aid, 0.5~1 parts of wetting agent, 3~6 parts of wear-resistant filler, 3~7 parts of flame retardant, 0.3 parts of triethanolamine, 0.3~0.6 parts of leveling agent, 5~10 parts of deionized water; The preparation process of the wear-resistant filler is as follows: Chitosan was dissolved in an acetic acid aqueous solution with a mass fraction of 5% to obtain a chitosan solution, wherein the mass fraction of the chitosan solution was 13-17%, the temperature was maintained at 65°C and the speed was 300r / min for 45min, tungsten carbide was continuously added, the speed was maintained for 2-5h, and the mixture was dried at 95-105°C for 8-12h to obtain pretreated tungsten carbide; 30-40 parts of pretreated tungsten carbide and 80-100 parts of toluene are uniformly mixed, and then 10-15 parts of polyamide wax are added, and stirred at a speed of 100-150 r / min for 40-60 min at room temperature, and the speed is increased to 300-500 r / min and stirred for 2-3 h, and then freeze-dried at -60°C for 6 h, and then ball-milled at a speed of 300 r / min for 3 h in a ball mill, and then passed through a 200-mesh sieve to obtain the wear-resistant filler; The preparation process of the flame retardant is as follows: The silane coupling agent KH550 was mixed with deionized water and ethanol in a volume ratio of 1:10 to prepare a KH550 solution with a mass fraction of 5-10%. Quartz sand was immersed in the KH550 solution, and then ultrasonically dispersed for 30 minutes, heated to 100 °C in a water bath and stirred for 1.5 hours. The dried solid was dried in a 95 °C constant temperature forced air drying oven for 10 hours to obtain a dry solid. The dried solid and polysilsesquioxane in a mass ratio of 20:(4-7) were then ground in a ball mill at a speed of 400 r / min for 4 hours to obtain modified quartz sand. Modified quartz sand, ammonium polyphosphate and zirconium phosphate in a mass ratio of (5-8):10:10 are ground by a ball mill at a speed of 300 r / min for 2 h to uniformly disperse them to obtain the flame retardant.

2. The wear-resistant flame-retardant automotive paint according to claim 1, characterized in that: The film-forming aid is dipropylene glycol methyl ether.

3. The wear-resistant flame-retardant automotive paint according to claim 1, characterized in that: The defoaming agent is one of BYK011, BYK022 and BYK024.

4. The wear-resistant flame-retardant automotive paint according to claim 1, characterized in that: The wetting agent is one of BYK349 ​​and BYK348.

5. The wear-resistant flame-retardant automotive paint according to claim 1, characterized in that: The leveling agent is polyether-modified polydimethylsiloxane.

6. A spraying process for a wear-resistant and flame-retardant automotive paint according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Pretreatment: Degreasing, decontamination and electrostatic dust removal are performed on the surface of the car, wherein the surface static voltage is less than 600 volts; S2, spraying primer: spray primer on the surface of the car after electrostatic dust removal, dry it at room temperature for 35-45 minutes, spray primer for the second time, continue drying and curing for 40-50 minutes to obtain a primer layer, wherein the parameters during spraying are: spraying pressure of 0.45-0.55MPa, spraying distance of 15-20cm; S3, spray paint: spray paint on the surface of the primer layer, dry it at room temperature for 40-50 minutes to form a paint layer, wherein the spraying pressure is 0.65-0.75MPa, and the spraying distance is 20-30cm; S4, spray paint: According to the weight proportions, waterborne polyurethane, triethanolamine and waterborne acrylic resin emulsion were stirred at a speed of 250 r / min for 30-40 min, and then wear-resistant filler and wetting agent were added and stirred for 35 min, and then flame retardant, defoaming agent and leveling agent were added and stirred at a speed of 350 r / min for 25-35 min, and finally film-forming aid and deionized water were added and stirred for 45 min to obtain topcoat; Spray the topcoat on the surface of the color paint layer and dry it at room temperature for 1-2 hours to form a topcoat layer. Control the spraying pressure to 0.9-1.1 MPa and the spraying distance to 30-45 cm. S5, drying: drying at 140-150° C. for 15-25 min to complete the spraying of the wear-resistant flame-retardant automotive paint.

7. The spraying process of the wear-resistant and flame-retardant automotive paint according to claim 6 is characterized in that: The thickness of the primer layer is 15-20 μm.

8. The spraying process of the wear-resistant and flame-retardant automotive paint according to claim 6 is characterized in that: The thickness of the color paint layer is 20-30 μm.

9. The spraying process of the wear-resistant and flame-retardant automotive paint according to claim 6, characterized in that: The thickness of the topcoat layer is 30-45 μm.

Citation Information

Patent Citations

  • Novel modified filler and preparation method thereof

    CN104475045A

  • Waterproof moisture-proof self-limiting temperature heat tracing cable

    CN106046480A

  • Anti-corrosion and fireproof antibacterial epoxy paint

    CN106752724A

  • Rat and ant bite resistant waterproof cable

    CN107141520A

  • High-strength anti-corrosion coating as well as preparation method and application thereof

    CN107141863A